Diabetic Ketoacidosis in Type 2 Diabetes Mellitus Patients with a History of Hypertension: Case Report - Tri Setyawati; Sarniwaty Kamissy; Wisnu Pradhana Merta (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Diabetes Mellitus Type 2 is a chronic hyperglycemic disease due to insensitivity of cells to insulin. High glucose levels can cause metabolic problems that occur due to abnormalities in insulin secretion resulting in symptoms of decreased consciousness, a condition known as diabetic ketoacidosis. One of the complications of diabetes is stroke caused by hypertension. This report describes a 69-year-old male patient who was diagnosed with type 2 diabetes mellitus with a history of hypertension who had decreased consciousness. Type 2 Diabetes Mellitus is a hyperglycemic disease due to insensitivity of cells to insulin. Diabetic ketoacidosis (DKA) is an emergency in diabetes mellitus (DM). One of the symptoms that appear such as decreased consciousness, hyperglycemia, Kussmaul breathing. Management should require correction of dehydration, hyperglycemia, acidosis and electrolyte abnormalities, identification of comorbid precipitating factors, and most importantly, continuous patient monitoring.